Unraveling family resilience patterns in ICU first-episode stroke: a latent profile analysis - Du, Jinlei; Yang, Jin; Wu, Yulian; Lei, Ling; Nie, Chencong; Wu, Xiaoling (Frontiers in Psychology, 2026)
ObjectiveTo identify latent family resilience profiles among families of patients with first-episode stroke in the intensive care unit (ICU) and examine factors associated with resilience heterogeneity, with the aim of informing targeted family-support interventions.MethodsA cross-sectional study was conducted among 335 ICU patients with first-episode stroke and their primary caregivers. Family resilience was assessed using the Chinese version of the Family Resilience Assessment Scale (FRAS-C). Latent profile analysis (LPA) was used to identify subgroups of family resilience, while LASSO regression and multiple binary logistic regression were applied to determine influencing factors.ResultsTwo distinct resilience profiles were identified: Developing Families, characterized by lower levels of communication, resource utilization, and positive outlook; and Optimized Families, characterized by higher resilience across all dimensions. ICU admission count (OR = 2.299, 95% CI: 1.066–4.960), frequency of care and support from relatives or friends (OR = 1.851, 95% CI: 1.068–3.206), and number of additional organ system dysfunctions (OR = 0.233, 95% CI: 0.122–0.445) were significantly associated with family resilience profiles (all P < 0.05).ConclusionFamily resilience among ICU first-episode stroke patients shows notable heterogeneity, with two typical resilience patterns. Early identification of high-risk families—particularly those with limited social support or higher disease complexity—can guide clinicians in delivering targeted communication support, psychological counseling, and resource linkage interventions. Tailored resilience-enhancing strategies may contribute to better patient recovery and improved family adaptation during critical care.